VARIABEL-VARIABEL YANG MEMPENGARUHI KINERJA GURU SEKOLAH DASAR NEGERI DI GUGUS 07 KOTA KEDIRI - Iing Sri Hardiningrum (Faculty of Social and Political Science, 2016)
The objective of this study is to evaluate the influence of style of leadership, competencies, and school atmosphare toword the teacher performence in seven group own state Prelementry School City District-Kediri City. Analysis instrument use in this study uses multiple linear regression analyse, which consist of teacher performance as dependent variables and style of leadership (X1), competencies (X2), and school atmosphare (X3) as independent variables. Determine the most independent factors that influence the teacher performance the researcher use T-test analyse, data collected from questioners, observations and school document. In this study, we found that teacher competencies is the most factors which influence the teacher performances. In this study, we found too that style of leadership, competency, and school atmosphere significant influence the teacher performance.